Average intensity and spreading of partially coherent model beams propagating in a turbulent biological tissue. (November 2016) - Wu, Yuqian; Zhang, Yixin; Wang, Qiu; Hu, Zhengda
Abstract: For Gaussian beams with three different partially coherent models, including Gaussian-Schell model (GSM), Laguerre-Gaussian Schell-model (LGSM) and Bessel-Gaussian Schell-model (BGSM) beams propagating through a biological turbulent tissue, the expression of the spatial coherence radius of a spherical wave propagating in a turbulent biological tissue, and the average intensity and beam spreading for GSM, LGSM and BGSM beams are derived based on the fractal model of power spectrum of refractive-index variations in biological tissue. Effects of partially coherent model and parameters of biological turbulence on such beams are studied in numerical simulations. Our results reveal that the spreading of GSM beams is smaller than LGSM and BGSM beams on the same conditions, and the beam with larger source coherence width has smaller beam spreading than that with smaller coherence width. The results are useful for any applications involved light beam propagation through tissues, especially the cases where the average intensity and spreading properties of the light should be taken into account to evaluate the system performance and investigations in the structures of biological tissue. Abstract : Highlights: Spatial coherence radius of a spherical wave propagating in a turbulent biological tissue is developed. Expressions of average intensity and beam spreading for GSM, LGSM and BGSM beams in a turbulent biological tissue are derived. The contrast for the three partially coherent model beams is shown in numerical simulations. The results are useful for any applications involved light beam propagation through tissues.